2015
DOI: 10.1578/am.41.4.2015.503
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing the Impact of Underwater Clearance of Unexploded Ordnance on Harbour Porpoises (Phocoena phocoena) in the Southern North Sea

Abstract: Large amounts of legacy unexploded ordnance (UXO) are still present in the North Sea. UXO are frequently accidentally encountered by fishermen and dredging vessels. Out of concern for human safety and to avoid damage to equipment and infrastructure from uncontrolled explosions, most reported UXO found in the Dutch Continental Shelf (DCS) are detonated in a controlled way. These underwater detonations produce high amplitude shock waves that may adversely affect marine mammals. The most abundant marine mammal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 49 publications
(105 reference statements)
0
36
0
1
Order By: Relevance
“…Instead, following Southall et al (2007), PTS-onset was defined as 164 dB re 1 µPa 2 s (= TTS onset SEL) + 15 dB = 179 dB re 1 µPa 2 s, and considered a lower limit below which PTS is unlikely to occur. Experi-mental exposure of fresh dead marine mammal carcasses to underwater explosives (Ketten 2004) showed that ear trauma can occur at peak over-pressures between 10 and 25 psi (or 69−172 kPa), which corresponds to approximately SEL 190 to 203 dB re 1 µPa 2 s for explosions in a shallow-water environment (von Benda-Beckmann et al 2015). It was therefore assumed that the explosion sound would very likely cause PTS at the lower limit at which ear trauma occurs (i.e.…”
Section: Hearing Loss Thresholdsmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, following Southall et al (2007), PTS-onset was defined as 164 dB re 1 µPa 2 s (= TTS onset SEL) + 15 dB = 179 dB re 1 µPa 2 s, and considered a lower limit below which PTS is unlikely to occur. Experi-mental exposure of fresh dead marine mammal carcasses to underwater explosives (Ketten 2004) showed that ear trauma can occur at peak over-pressures between 10 and 25 psi (or 69−172 kPa), which corresponds to approximately SEL 190 to 203 dB re 1 µPa 2 s for explosions in a shallow-water environment (von Benda-Beckmann et al 2015). It was therefore assumed that the explosion sound would very likely cause PTS at the lower limit at which ear trauma occurs (i.e.…”
Section: Hearing Loss Thresholdsmentioning
confidence: 99%
“…controlled underwater detonations of recovered bombs, mines and torpedoes from WWII) are unique as they represent single sound events, with the peak sound pressures of the blast wave being one of the highest anthropogenic sound levels produced in the marine environment (Ainslie et al 2009, Koschinski 2011. Such detonations are conducted on the Dutch Continental Shelf (DCS) by the Royal Netherlands Navy in a controlled manner, to reduce the risk of uncontrolled explosions, which could be dangerous to human life and infra-structure (Koschinski 2011, von Benda-Beckmann et al 2015. Each year, approximately 100 detonations occur on the DCS.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations